Extracellular Mitochondrial DNA and N-Formyl Peptides in Trauma and Critical Illness: A Systematic Review. Issue 12 (December 2018) - Lubkin, David T.; Bishawi, Muath; Barbas, Andrew S.; Brennan, Todd V.; Kirk, Allan D.
Abstract : Objectives: Extracellular mitochondrial DNA and N-formyl peptides released following tissue damage may contribute to systemic inflammation through stimulation of the innate immune system. In this review, we evaluate existing in vivo human data regarding a role for mitochondrial DNA and N-formyl peptides in producing systemic inflammation in trauma and critical illness, investigate the utility of these molecules in risk prediction and clinical decision support, and provide suggestions for standardization of future research. Data Sources: PubMed, Embase (1971–2017). Study Selection: Studies measuring extracellular mitochondrial DNA and/or N-formyl peptides in acutely ill patients. Data Extraction: Fifty-four studies were analyzed. Data extracted included article characteristics, methods, results, and performance in clinical prediction. Data Synthesis: The most common patient types investigated were trauma (19 studies) and sepsis (eight). In studies comparing patient mitochondrial DNA or N-formyl peptide levels to healthy controls, 38 (90.5%) reported significantly elevated mitochondrial DNA levels in patients at first reported time point, as did the one study making this comparison for N-formyl peptides. Nine studies (81.8%) reported significantly elevated plasma/serum mitochondrial DNA levels in at least one time point in patients who developed inflammatory complications of their primary pathology compared with patients without inflammatory complications. For the ability of mitochondrial DNA to predict complications or outcomes, the area under the curve was 0.7 or greater in 84.6% of receiver operating characteristic curves, and 92.9% of odds, adjusted odds, risk, and hazard ratios were statistically significant. Conclusions: Extracellular mitochondrial DNA levels are elevated early in patients' hospital courses in many acute illnesses and are higher in patients who develop inflammatory complications. Elevated mitochondrial DNA levels may be clinically useful in risk prediction and clinical decision support systems. Further research is needed to determine the role of extracellular N-formyl peptides in systemic inflammation and their possible clinical utility. Abstract : Supplemental Digital Content is available in the text.